2016
DOI: 10.1016/j.virol.2015.10.029
|View full text |Cite
|
Sign up to set email alerts
|

A novel rabies vaccine based-on toll-like receptor 3 (TLR3) agonist PIKA adjuvant exhibiting excellent safety and efficacy in animal studies

Abstract: Vaccination alone is not sufficiently effective to protect human from post-exposure rabies virus infection due to delayed generation of rabies virus neutralizing antibodies and weak cellular immunity. Therefore, it is vital to develop safer and more efficacious vaccine against rabies. PIKA, a stabilized chemical analog of double-stranded RNA that interacts with TLR3, was employed as adjuvant of rabies vaccine. The efficacy and safety of PIKA rabies vaccine were evaluated. The results showed that PIKA rabies va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…RABV-derived lipopeptide CE536 conjugated to a TLR7 agonist (imiquimod) was reported to have improved DC phenotypic maturation and the Th1-biased humoral immune response in mice [42]. The TLR3 agonist PIKA (a chemical analog of double-stranded RNA) as an adjuvant of the rabies vaccine enhanced both humoral and cellular immunity [14]. The synthetic TLR9 agonist IMO-2170 increased the magnitude of the humoral immune response induced by the rabies vaccine [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RABV-derived lipopeptide CE536 conjugated to a TLR7 agonist (imiquimod) was reported to have improved DC phenotypic maturation and the Th1-biased humoral immune response in mice [42]. The TLR3 agonist PIKA (a chemical analog of double-stranded RNA) as an adjuvant of the rabies vaccine enhanced both humoral and cellular immunity [14]. The synthetic TLR9 agonist IMO-2170 increased the magnitude of the humoral immune response induced by the rabies vaccine [12].…”
Section: Discussionmentioning
confidence: 99%
“…So far, the aluminum adjuvant for inactivated rabies vaccine is under pre-clinical study [12], and the PIKA (a synthetic double-stranded RNA analogue) adjuvant has progressed to a phase II trial in healthy adults [13]. PIKA-containing rabies vaccine is more effective in preventing rabies due to its ability to activate the Toll-like receptor 3 (TLR3) pathway compared to adjuvant-free vaccines [14].…”
Section: Introductionmentioning
confidence: 99%
“…1B), no significant CTL elevation was detected (Fig. 3B), possibly because cationic lipids delay the release of Cramp and Ag, 17 resulting in the ability of Cramp remnants to kill tumor cells by enhancing the proliferation and activation of natural killer cells but not CD4C or CD8C T cells. 35 Delayed antigen release is one mechanism utilized by adjuvants.…”
Section: Discussionmentioning
confidence: 97%
“…The activation of these receptor-mediated signal pathways boosts downstream acquired immunity, particularly T cell responses aimed at eliminating virus-infected cells. [15][16][17] Experimental and clinical trials using Poly I:C as an adjuvant have elicited good effects for the treatment of several cancers, including thymomas and melanomas. 18,19 Notably, some studies showed only good effects in combination with PD-1 (programmed cell death protein 1) blockade.…”
Section: Introductionmentioning
confidence: 99%
“… 29 In the US, PolyI:C has been used in rintatolimod (Ampligen) in several clinical trials (for HIV and chronic fatigue syndrome, among others) but was not approved by the U.S. Food and Drug Administration due to controversial clinical outcomes, and no additional trials were carried out. In China, a rabies vaccine with PolyI:C showed promising safety and efficacy in preclinical studies 30 and phase 1 clinical trials. In addition, several studies have recently shown that Poly I:C can be a safe and effective adjuvant for improving both humoral and cellular immunity in animals.…”
Section: Introductionmentioning
confidence: 99%